(Table 1) 137Cs and 90Sr concentrations, salinity, and temperature in waters of the southeastern Baltic Sea on October 16, 2001 - D Styro; R Morkuniene; S Vdovinskiene (PANGAEA, 2006)
An analysis of variations in 137Cs and 90Sr concentrations in Baltic Sea surface waters after the accident at the Chernobyl nuclear power plant was performed. Instability of 137Cs concentrations during the short-term observations was found, when they differed 2- to 3-fold. Concentrations of 90Sr appeared to be more stable; meanwhile, their deviations sometimes exceeded ranges of experimental errors. By variations in the monthly average values of radionuclide concentrations in surface waters of the Baltic Sea in 1989-1995, no trend of water self-purification was observed. Theoretical results obtained confirmed a potential of formation and propagation of patches with increased concentrations of 137Cs in the southeastern Baltic Sea. The most reliable factor that controlled the process of self-purification of Baltic Sea water appeared to be the mean annual value of radionuclide concentration. Pronounced divergences were obtained between the measured and calculated mean annual concentrations of 137Cs and 90Sr in surface waters of the Baltic Sea in 1989-2001. These divergences are explained by potential influence of waters from the Gulf of Bothnia and by other additional supplies of radionuclides to marine environment, which were not included into mathematical models.
Supplement to: Styro, D et al. (2006): The process of self-purification of the Baltic Sea waters from artificial radionuclides. Oceanology, 46(3), 358-367, https://doi.org/10.1134/S0001437006030076